The influence of temperament style on a student's choice of and performance in a computer programming course. - Blignaut, Pieter; Naude, Annelie (Computers in Human Behavior, 2008)
This study is an attempt to determine whether it is necessary to include temperament style when compiling an instrument to predict a student's chances of success in a computer programming course. Temperament style is seen as the combination of qualities which constitute the natural disposition of an individual and which affect actions, thinking and emotions. The DISC model, as adapted by Boyd [Boyd, C. F. (1994). Different children, different needs: the art of adjustable parenting. Oregon: Questar Publishers Inc.], views people as behaving along two orthogonal dimensions: the speed at which a person moves through life, and his/her general focus when doing things, i.e. on people or on tasks. This study proved that both of these dimensions have an influence on the performance of students in a computer programming course while one of them also has an influence on a student's choice to pursue a programming course. Copyright (c) 2008 Elsevier Ltd.